From Agasa Cristie to Group Image Play-Analysis of Horror Survival Game Panic Room : Escaping from the Den on Emotional Elements Development - Doo Heon Song; Hae Kyung Rhee; Ji-eun Kim; Jong Hee Lee (Institute of Advanced Engineering and Science, 2018)
A maniac computer game genre called